The Ability of Junior High School Mathematics Teachers in Kampar Regency in Developing Higher Order Thinking Skills - Meldawati Meldawati; Maimunah Maimunah; Yenita Roza Yenita Roza (Universitas Negeri Makassar, 2020)
Higher Order Thinking Skills are one of the skills that students must master in facing complex situations. These skills can be applied by teachers through Math learning at the junior high school level, therefore Math teachers must be able to facilitate students for Higher Order Thinking Skills questions. The purpose of this study is to identify the ability of the junior high school Math teachers in Kampar Regency in developing HOTS questions. A total of 30 teachers were asked to fill out a questionnaire and compile 2 HOTS questions. The results of the questionnaire were described and the questions made by the teachers were analyzed based on three aspects, namely 1) the topics chosen by the teacher; 2) the classification of questions based on dimensions of cognitive processes; and 3) the classification of questions that meet the Higher Order Thinking Skills category. The findings showed that the teachers chose a variety of topics including numbers, algebra, geometry and measurement, statistics and probability. Based on the dimensions of the Bloom Taxonomy cognitive process, the questions prepared by the teachers include understanding, implementing, analyzing, and evaluating. 25% of the questions were categorized as Higher Order Thinking Skills questions.Keywords:Junior high school teachers’ability;Higher Order Thinking Skills; problem constructing